PULMONARY REHABILITATION FOR CHRONIC OBSTRUCTIVE PULMONARY DISEASE: A CASE REPORT - Ajitirtiono, Ramadanu; Herawati, Isnaini (Universitas Muhammadiyah Surakarta, 2021)
Introduction: Global Initiative for Chronic Obstructive Lung Disease (GOLD) defined chronic obstructive pulmonary disease (COPD) as a common, preventable, and treatable disease characterized by persistent respiratory symptoms and airflow limitation. In COPD, the respiratory muscles remain contracted for prolonged periods to meet the increased demand of ventilatory flow causing hyperinflation and increasing load on the respiratory muscle. Pulmonary rehabilitation (PR) is defined as a comprehensive individualized intervention provided by an interdisciplinary team that targeting COPD patients to achieve the maximal level of independence, functioning and, autonomy. PR is a key component of managing COPD because it has been shown to improve exercise capacity, dyspnea, and quality of life in patients with moderate to severe COPD. Physical therapy is a part of PR that can improve multiple aspects of physical function and the performance of functional activities in COPD Patients Case Presentation: A 56-year-old female patient with a longstanding history of asthma, was referred to Balai Besar Kesehatan Paru Masyarakat (BBKPM) Bandung due to shortness of breath. The shortness of breath worsened three days ago when performing activities and was not affected by changes in the body position. The shortness of breath limits the patient's ability to walk more than 50 m. The patient must stop and rest for a while before being able to walk again Management and Outcome: A pulmonary rehabilitation program twice a week in 3 weeks was given which consists of breathing exercise, respiratory muscle stretching, and aerobic training. After 6 sessions of physical therapy, there is improvement in chest expansion, 6MWT distance, mMRC score, and CAT score. Discussion: Patients with chronic obstructive pulmonary disease usually having shortness of breath, reduced functional capacity, and quality of life. Evidence suggests that PR is an effective intervention for patients with COPD. Expected benefits from physical therapy are reduced dyspnea level, improved exercise tolerance, and maximized patient’s health-related quality of life. Conclusion: A pulmonary rehabilitation program consisting of breathing exercise, respiratory muscle stretching, and aerobic training was able to improve chest expansion, improve 6MWT distance, reducing mMRC dyspnea scale, and reducing CAT score.